PENINGKATAN KEMAMPUAN LITERASI ANAK SEKOLAH DASAR MELALUI PROGRAM GLS (GERAKAN LITERASI SEKOLAH) - Hasna Khalishah Fadhilah; Dianita Widya Syaqina; Zaskia Nafasabilla; Decenni Amelia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to determine the improvement of elementary school children's literacy through the GLS (School Literacy Movement) program. This research uses a qualitative method with a literature study approach that aims to describe the findings of researchers on several scientific journal articles found according to the topic of discussion so that the results of the discussion are obtained. The results showed that the GLS program has a positive impact on improving the literacy skills of elementary school children through three stages in its implementation, namely the habituation stage, the development stage and the learning stage. The GLS program encourages students to participate in active reading activities, such as reading books outside formal lessons. GLS succeeds in attracting students' attention to read more through the provision of interesting reading books, such as illustrated stories, educational comics, and other reading materials that are appropriate for their age. With the routine implementation of the GLS program, it can provide an increase in reading and writing skills, as well as the growth of interest in reading, especially among elementary school children.